Musculoskeletal Ultrasound Diagnosis in Calcium Pyrophosphate Dihydrate Crystal Deposition Disease - MUȘETESCU, ANCA EMANUELA (Curr Health Sci J, 2014)
Calcium pyrophosphate dihydrate (CPPD) crystal deposition disease is extremely versatile. We present the case of a 52 years old patient referred for inflammatory pain of the left knee and ankle of recent onset with intense inflammatory syndrome that mimics rheumatoid arthritis. Musculoskeletal ultrasound was able to detect effusion, hyperechoic crystals within the cartilage and fibrocartilage, inside tendons, suggestive for CPPD disease and to guide fluid aspiration as well as in sustaining a rapid diagnosis corroborating images suggestive for CPPD disease to biological data – hypercalcemia and hyperparathyroidism in finding the predisposing condition, the parathyroid adenoma.